2012
DOI: 10.1038/ki.2011.347
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol improves renal microcirculation, protects the tubular epithelium, and prolongs survival in a mouse model of sepsis-induced acute kidney injury

Abstract: The mortality rate of patients who develop acute kidney injury during sepsis nearly doubles. The effectiveness of therapy is hampered because it is usually initiated only after the onset of symptoms. As renal microvascular failure during sepsis is correlated with the generation of reactive nitrogen species, the therapeutic potential of resveratrol, a polyphenol vasodilator that is also capable of scavenging reactive nitrogen species, was investigated using the cecal ligation and puncture (CLP) murine model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(158 citation statements)
references
References 60 publications
3
153
0
2
Order By: Relevance
“…21,26 Similarly, rodent models of acute endotoxemia suggest that cortical peritubular capillaries are among the first renal structures injured. [27][28][29][30] Interestingly, despite an apparent full recovery of renal function at 48 hours, functional capillary density recovered only partially. 27 Moreover, areas of compromised cortical microvascular perfusion have been shown to correlate with renal tubular cell stress in corresponding regions, suggesting important links between altered peritubular microcirculation and epithelial cell dysfunction.…”
Section: Peritubular Microcirculation In Akimentioning
confidence: 99%
See 1 more Smart Citation
“…21,26 Similarly, rodent models of acute endotoxemia suggest that cortical peritubular capillaries are among the first renal structures injured. [27][28][29][30] Interestingly, despite an apparent full recovery of renal function at 48 hours, functional capillary density recovered only partially. 27 Moreover, areas of compromised cortical microvascular perfusion have been shown to correlate with renal tubular cell stress in corresponding regions, suggesting important links between altered peritubular microcirculation and epithelial cell dysfunction.…”
Section: Peritubular Microcirculation In Akimentioning
confidence: 99%
“…Oxidative stress-mediated cellular injury has been implicated in the pathogenesis of AKI as a central element of the network of danger response, affecting both endothelial and epithelial functions as well as cellular energetics. 33 Therapeutic interventions aimed at maintaining the homeostatic balance between oxygen radicals, nitric oxide, and oxygen have been shown to be effective in several studies in rodent models of septic AKI [27][28][29][30][31] and ischemia-reperfusion injury 52 as well as in large animal models of septic AKI. 53,54 The lack of effective inducible nitric oxide synthase inhibitors for clinical use can be considered an important area for research.…”
Section: Targets To Protect the Nephrovascular Unitsmentioning
confidence: 99%
“…Nevertheless, peritubular flow has been found to be sluggish and congested, probably as the result of a high capacity and low resistance circulation [9]. Other theories about the GFR decline during sepsis have focused on the reduction of filtration pressure not necessarily associated with glomerular hypoperfusion; renal and central (CVP) venous pressures are frequently increased in sepsis as a possible consequence of the so-called fluid challenge of septic patients in the first hours after ICU admission.…”
Section: Tubular Injury Glomerular Injurymentioning
confidence: 99%
“…And it has been suggested that the in vivo biological activity of equimolar doses of Pte may be greater than that of resveratrol (6), and the antioxidant activity of Pte are superior to resveratrol due to its higher lipophilicity, which increases its ability to be absorbed compared to resveratrol (6). Studies have demonstrated that resveratrol has salutary effect on sepsis-induced multiple organ dysfunction, such as myocardial depression (7), AKI (8)(9)(10). However, the effect of Pte on sepsis-induced AKI remains unclear.…”
Section: Introductionmentioning
confidence: 99%